Surgical Wound Dehiscence Treatment: Tata Laksana Dehisensi Luka Operasi - Dewita Nilasari; Riyan H. Kurniawan; Ni Putu C. D. Atmantika; Achmad K. Harzif (Indonesian Socety of Obstetrics and Gynecology, 2023)
Objective: This article describes management of surgicalwound dehiscence. in a cesarean section.Method: Case report.Case: A 39 years-old woman, P4, presented with reddish puscoming out from open surgical wound on day 4 following acaesarean section. Laboratory fi ndings revealed a conditionof Hypoalbuminemia, leukocytosis, and a Staphylococcusaureus was detected on pus from the wound base. Upon theresuturing, the wound was dressed with antimicrobial wounddressings and pad and changed every 12 hours. After 3 days,the wound was dressed with modern antimicrobial wounddressings gel and pad, changed every 3 days and plannedfor necrotomy afterwards. A presence of dry, granulationtissue was observed before the resuturing.Conclusion: Selection of dressing regimen shouldbe individualized according to the wounds. Modernantimicrobial wound dressing can be a good therapy optionfor surgical wound dehiscence after caesarean section.Keywords: surgical site infection, surgical wound, wounddehiscence.Tujuan: Artikel ini melaporkan tata laksana dehisensi lukaoperasi seksio sesarea.Metode: Laporan kasus.Kasus: Seorang perempuan 39 tahun, P4, datang dengankeluhan nanah kemerahan keluar dari luka operasi terbukapostoperasi seksio sesarea hari ke-4. Temuan laboratorium:Hipoalbuminemia, leukositosis, dan Staphylococcusaureus dari kultur dasar luka. Sebelum operasi penjahitankembali, luka dibalut dengan pembalut dan bantalan lukaantimikroba modern yang diresapi dengan hidrogel, digantisetiap 12 jam. Setelah 3 hari, luka dibalut dengan gel danpembalut luka antimikroba modern yang diresapi denganhidrogel, diganti setiap 3 hari dan direncanakan untuknekrotomi. Sebelum operasi dilakukan kembali, luka tampakkering dengan dasar jaringan granulasi.Kesimpulan: Regimen pembalutan harus disesuaikandengan kebutuhan masing-masing luka. Pembalut lukaantimikroba modern dapat menjadi pilihan terapi yang baikuntuk dehisensi luka bedah setelah operasi seksio sesarea.Kata kunci: dehisensi luka, infeksi luka operasi, luka operasi.